1, 1‐Dilithioethylene: Toward Spectroscopic Identification of the Definitive Singlet Ground Electronic State of a Peculiar Structure. Issue 11 (1st April 2016) - Liu, Yameng; Wang, Xiao; Liu, Yongdong; Zhong, Rugang; Xie, Yaoming; Schaefer, Henry F.
Abstract: 1, 1‐Dilithioethylene is a prototypical carbon–lithium compound that is not known experimentally. All low‐lying singlet and triplet structures of interest were investigated by using high‐level theoretical methods with correlation‐consistent basis sets up to pentuple ζ. The coupled cluster methods adopted included up to full triple excitations and perturbative quadruples. In contrast to earlier studies that predicted the twisted C 2 v triplet to be the ground state, we found a peculiar planar Cs singlet ground state in the present research. The lowest excited electronic state of 1, 1‐dilithioethylene, the twisted Cs triplet, was found to lie 9.0 kcal mol −1 above the ground state by using energy extrapolation to the complete basis set limit. For the planar Cs singlet and twisted Cs triplet states of 1, 1‐dilithioethylene, anharmonic vibrational frequencies were reported on the basis of second‐order vibrational perturbation theory. The remarkably low (2050 cm −1 ) C−H stretching fundamental (the C−H bond near the bridging lithium) of the singlet state was found to have very strong infrared intensity. These highly reliable theoretical findings may assist in the long‐sought experimental identification of 1, 1‐dilithioethylene. Using natural bond orbital analysis, we found that lithium bridging structures were strongly influenced by electrostatic effects. All carbon–carbon linkages corresponded to conventional double bonds. Abstract : Run to ground : The lowest‐energy singlet and triplet states of 1, 1‐dilithioethylene are optimized at the CCSD(T)/cc‐pVQZ level of theory. A planar Cs singlet ground state is found in the present research. Natural bond orbital analysis indicates that lithium‐bridging structures are strongly influenced by electrostatic interactions. Overall, this research should assist the future experimental characterization of the prototypical 1, 1‐dilithioethylene molecule.